The Role of Teachers through a Religious Coping Model in Addressing Student Delinquency - Kevin Andrew Pranata Perangin Angin (Yayasan Bayt Shufiya Nusantara, 2023)
Student disciplinary infractions in Madrasah yield complex socio-pedagogical implications, necessitating the development of robust models and strategic interventions for their resolution. This study aims to explain the religious coping strategies implemented by Aqidah Akhlak teachers in handling student delinquency at MTs Taman Pendidikan Islam Medan. This research employed a qualitative approach using a field study design. Data were collected through open and closed interviews with teachers and students as key informants, as well as observations of various religious habituation activities within the madrasah environment. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that the religious coping strategy in this madrasah was systematically developed through the identification of various forms of student delinquency, which were subsequently addressed through the establishment of religious habituation programs such as the recitation of Asmaul Husna, morning religious talks (kultum), Qur’anic recitation (tadarus Al-Qur’an), congregational prayers, and tahfidzul Qur’an. These programs function as mechanisms for strengthening spiritual values that are not only preventive and corrective in nature, but also contribute to the formation of a sustainable religious ecosystem within school life. This study contributes to the understanding that religious coping practices play a significant role in strengthening students’ moral and psychological resilience in overcoming delinquent behavior.